Pain pharmacogenetics - Slepukhina, Mariia A.; Ivashchenko, Dmitriy V.; Sheina, Maria A.; Muradian, Andranik Alexandrovich; Blagovestnov, Dmitriy Alexeevich; Sychev, Dmitriy A. (Drug metabolism and drug interactions, 2020)
Pain is a significant problem in medicine. The use of PGx markers to personalize postoperative analgesia can increase its effectiveness and avoid undesirable reactions. This article describes the mechanisms of nociception and antinociception and shows the pathophysiological mechanisms of pain in the human body. The main subject of this article is pharmacogenetic approach to the selection of anesthetics. Current review presents data for local and general anesthetics, opioids, and non-steroidal anti-inflammatory drugs. None of the anesthetics currently has clinical guidelines for pharmacogenetic testing. This literature review summarizes the results of original research available, to date, and draws attention to this area.